Sub-nanometer resolution of an organic semiconductor crystal surface using friction force microscopy in water. (2nd March 2016) - Pimentel, Carlos; Varghese, Shinto; Yoon, Seong-Jun; Park, Soo Young; Gierschner, Johannes; Gnecco, Enrico; Pina, Carlos M
Abstract: Organic semiconductors (OSC) are attracting much interest for (opto)electronic applications, such as photovoltaics, LEDs, sensors or solid state lasers. In particular, crystals formed by small -conjugated molecules have shown to be suitable for constructing OSC devices. However, the (opto)electronic properties are complex since they depend strongly on both the mutual orientation of molecules as well as the perfection of bulk crystal surfaces. Hence, there is an urgent need to control nano-topographic OSC features in real space. Here we show that friction force microscopy in water is a very suitable technique to image the free surface morphology of an OSC single crystal (TDDCS) with sub-nanometer resolution. We demonstrate the power of the method by direct correlation to the structural information extracted from combined single crystal (SC-) and specular (s-) XRD studies, which allows us to identify the pinning centers encountered in the stick-slip motion of the probing tip with the topmost methyl groups on the TDDCS surface.